Inovasi Bank Syariah Indonesia dalam Peningkatan Minat Nasabah untuk Menabung di Lembaga Keungan Syariah - Supandi, Ach. Faqih; Umbaran, Bastomi Dhani; Azakia, Kiki (OECONOMICUS Journal of Economics, 2023)
Today internet banking is a major concern and a revolutionary weapon of strategic bank operations, for mendelivery as well as for interbank competition. Online banking was introduced as a channel where bank customers can conduct banking financial activities electronically through the bank's website. The approach used in this research is to use a qualitative approach using a type of Life History research (life story experience) where this research focuses on phenomena that occur in the field in certain situations. The result of this study is that Internet Banking has several conveniences in making transactions, including Account Information, Balance Information, Account Mutation, Fund Transfer, Transfer Between Rek, Transfer To Bang Lain, Scheduled Transakasi, Add Transfer And View Status so that the conveniences possessed by this application have a very significant influence on the interests of customers